Mainstreaming Child-Friendly Mosques In Banda Aceh, Yogyakarta And Batam - Rustam; Akamluddin Syahputra; Fahri Roja Sitepu (Islam Realitas: Journal of Islamic and Social Studies, 2025)
The study aims to reveal the perspectives and interpretations of informants related to their involvement in mainstreaming the concept of child-friendly mosques. This research is a follow-up to our previous study on the concept of child-friendly mosque management. Therefore, this research explores the informants’ experiences during the process of mainstreaming this concept and reveals how they interpret their lived experiences within that process. Consequently, this study employs a phenomenological qualitative approach, which is used to explore informants’ interpretations of their life experiences. Data was collected through three well-known qualitative methods: observation, in-depth interviews, and focus group discussions. The findings show that informants hold different views, experiences, and understandings regarding the presence of children in mosques and the mainstreaming process in which they participate. The presence of children in mosques, as part of the process of familiarizing them with places of worship, presents its own challenges for mosque management and congregations. Mentoring children, strengthening mosque management, and maintaining communication with the congregation can reduce emerging resistance and reinforce the positive value of children’s presence in mosques